Efficacy Of Oral Passive Immunotherapy Against Dental Caries In Humans Using Chicken Egg Yolk Antibodies Generated Against Streptococcus Mutans - C. GANDHIMATHI; A. MICHAEL (International Journal of Pharma and Bio Sciences, 2015)
Dental caries an ever growing public health problem is not much amenable to existing preventive measures. The aim of this study was to compare and evaluate the effectiveness of mouth rinse containing chicken egg yolk antibodies generated against whole cell antigen and cell associated glucosyltransferase enzyme (CA-GTF) of Streptococcus mutans in preventing recolonization of S.mutans in dental plaque of human volunteers. The experimental period was up to 210 days. At the end of the experimental period, in the experimental group treated with IgY to whole cell S.mutans reduction in reestablishment of S.mutans from base line value was 67.66% and the group treated with IgY to CA-GTF it was 89.66%. But in the control group treated with non-immune IgY reestablishment was greater than its baseline value with the increment of 9.67%. The promising results in the experimental studies vividly reveal that immune IgY to CA-GTF has significant influence in preventing caries development.